As chimney sweepers come to dust - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2015)
"Flavia rules! In this New York Times bestselling series of enchanting mysteries, youthful chemist and aspiring detective Flavia de Luce once again brings her knowledge of poisons and her indefatigable spirit to solve dastardly crimes -- but this time, she leaves behind her beloved English countryside, and takes her sleuthing prowess to the unexpectedly unsavory world of Canadian boarding schools!"--